Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Standard view
Full view
of .
0 of .
Results for:
P. 1
AP Calculus Section 4-5 U-Substitution and Change of Variable

# AP Calculus Section 4-5 U-Substitution and Change of Variable

Ratings: (0)|Views: 67|Likes:
AP Calculus Section 4-5 U-Substitution and Change of Variable
Calc Section 4-5 U-substitution and change_of_variable.doc

AP Calculus - Anthony
AP Calculus Section 4-5 U-Substitution and Change of Variable
Calc Section 4-5 U-substitution and change_of_variable.doc

AP Calculus - Anthony

### Availability:

See more
See less

05/27/2010

pdf

text

original

U-SUBSTITUTION
Pattern Recognition:The whole idea revolves around the “undoing” of thechain rule. The fact that the chain rule placesanother term as a multiplier onto an initial derivativemeans that we
need
that additional term to be therein order to “undo” the process.Symbolically:Since
[ ( ( ))] [ ( )] ( ( )) ( ) ( )
d  F g x F u F g x g x F u udx dx
′ ′ = = =
We can conclude
( ( )) ( ) ( ) ( ( )) ( )
F g x g x dx F u u dx F g x C F u
= = + = +
∫
The rule in our textbook may look a bit strange, or not saying much, but carefully examine the “If” part.
If ( ), then ( ) and
u g x du g x dx
= =
( ) ( )
f u du F u
= +
∫

Let’s examine the following examples on the board.What is the
u
? What is the
du
? After some time,this mechanical process should not always benecessary.
EXAMPLE 1:
2 2
( 1) (2 )
x x dx
+
∫
2
12
u xdu x
= +=
3 2 32 2 2
( 1)( 1) (2 )3 3
u x x x dx u du C
++ = = + = +
∫
EXMPLE

2:
5cos5
xdx
∫
EXAMPLE 3:
2 2
( 1)
x x dx
+
∫
EXAMPLE 3B: What you are FORBIDDEN TO DO:
2 2
( 1)
x dx
+
∫
2 2
1( 1) (2 )2
x x dx x
+
∫

CHANGE OF VARIABLES
Sometimes an integral is more manageable with acomplete change in variable. This followingexample is not one in which it is
necessary
to dothis, but simply illustrates the technique in an easyfashion.
EXAMPLE 4:
2 1
x dx
∫
OK, we will simply use the following to replace the major  portion of the integral.
2 1
u x
=
But, the way we will now go is to isolate
x
, in order tothen differentiate and get
dx
.
2
2 1
u x
=
2
1 2
u x
+ =
2
12
u x
+=
2
1( 1)2
x u
= +
dx udu
=
So,
32332
3132 12 12 13( )
uu du dx udu x u x x
= = = + =+ =+
∫